Review on analysis of soil moisture changes caused by coal mining subsidence in arid and semi-arid areas and their potential effects on plant physiology and ecology - ZHANG Xuyang; LIU Ying; LONG Linli; SU Yongdong; CHEN Dongxing; CHEN Xiaoyang (浙江大学学报. 农业与生命科学版)
Soil moisture is a key factor that restricts plant growth. Coal mining subsidence causes cracks on the ground, coupled with the reduction of groundwater level, which further reduces the already low soil moisture content in arid and semi-arid areas. When the soil moisture content is lower than the drought stress threshold of plants, it will inevitably affect plant physiology and ecology. This article first analyzed the impact of coal mining subsidence on the water environment, and then summarized the potential changes of plant physiological and ecological indicators when the soil moisture content was less than the plant drought stress threshold, including leaf and root morphologies, photosynthetic physiological indicators, osmotic adjustment substances, water physiological indicators, antioxidant enzyme activities, and components and contents of drought-resistant proteins. In the future, it should strengthen the monitoring of the coordinated changes in soil moisture and plant physiology and ecology in the arid and semi-arid areas, and strive to reveal the response mechanism of plant physiology and ecology to soil moisture changes caused by coal mining subsidence, as well as strengthening the research on the prediction model of the impact of coal mining on vegetation physiology and ecology in arid and semi-arid areas.